Divisia index monetary aggregates : Do they matter for monetary policy in Malaysia? - Dahalan, Jauhari (Universiti Utara Malaysia, 2004)
Divisia for narrowly and broadly defined monetary aggregate of a developing countty, Malavsia, are constructed. Unlike the Divisia for narrowly defined monetary aggregate MI, the Divisia for broader defined monetaty aggregate M2 does show significant differences in both level and growth rates that signified the degree of the important and usefulness of Divisia index in formulating the monetaty policy. We ascertained that there exist long-run relationships between all measures of monetary aggregates in this study with inflations. By constructing dynamic error-correction models for all the alternative measures of monetary aggregates, we performed out-of-sample forecasting for three different periods. Analysis of the forecasting statistics indicates that the Divisia monetary aggregates performed better than their simple-sum counterparts in forecasting ability. We conclude that Divisia monetary aggregate namely Divisia M2, has the best forecast ability among all. As such, Divisia M2 can serve as an excellent candidate as a target or indicator in formulating the monetary policy for Malaysia.